RASIONALITAS NARATIF DALAM MEMORI ALTERNATIF MEDIA (Pembingkaian Peristiwa 1965 pada Berita Media Daring) - Muhammad Aswan Zanynu (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2018)
Technology is not always related to hardware, but also related to its optimal use. Online news media has a number of advantages that are not owned by conventional media, such as space availability. In presenting an event in the past, news sites can technically provide alternative narratives. It is important to reveal how the online news media presents a number of important events in 1965. The focus of the study is emphasized on the aspect of narrative rationality. Using framing analysis of a number of articles in nine news sites, the study found that the arguments presented do not fully satisfy aspects of “coherence” and “fidelity”. There is still an incompatibility of substance when compared to other texts. Similarly, the alternative variations of memory presented are still more often a repetition of a number of known things. The support of media technology can not be utilized to improve the quality of the narrative presented over the past.